Unusual congenital goiter due to maternal Hashimoto thyroiditis: a case report - Català, Laura; Casas, Judit; Yeh, Sean; Josa-Eritja, Maria; Tirado-Capistros, Mireia; Moliner, Elisenda; Carreras, Gemma (Frontiers in Pediatrics, 2024)
Congenital hypothyroidism (CH) is the most common cause of endocrinopathy in the newborn Its incidence lies between 1 in 3000 and 1 in 2000, However, congenital goiter is a rare form of presentation.Hypothyroidism secondary to autoimmune etiology is extremely rare, with an incidence of 1:84.700 to 1:31.000 newborns. Anti-thyroid peroxidase antibodies (TPOAb) are able to cross the placenta but rarely induce hypothyroidism in the newborn, much less goiter.A case of congenital goiter in a male newborn secondary to maternal high TPOAb levels is reported.The mother was diagnosed of Hashimoto thyroiditis prior to the pregnancy. At birth, a grade 3 goiter was detected in the newborn.Laboratory testings revealed hypothyroidism with free thyroxine of 7,6 pmol/L, thyroid-stimulating hormone of 108mUI/L and high TPOAb levels. Treatment with Levothyroxine was started the second day of life with progressive thyroid function normalization. Neurological development has been normal until the date.